Morfofisiologia de mudas de eucalipto em resposta à aplicação de Stimulate® - Souza, Fabyana Cruz (2021)
Biostimulants consist of a combination of growth regulators, which when used in plants can alter and improve physiological and biometric processes. Stimulate® is a biostimulant made up of the following vegetable regulators: indole butyric acid - IBA (0.005%), which transforms into indoleacetic acid and favors cell elongation; kinetin (0.009%), which induces cell division; and gibberellic acid (0.005%), which acts in several metabolic pathways of plant development and 99.98% of inert ingredients. This study was based on the hypothesis that spraying with Stimulate® can be an alternative to accelerate the initial growth of eucalyptus seedlings. The work was carried out in a greenhouse with the objective of evaluating the application of different doses of Stimulate®, applied three times during the study, via the leaves in the eucalyptus (Eucalyptus urophylla) crop, genetic material I-144 (AEC 0144), through physiological and biometric variables. The experiment was designed as a completely randomized, with 6 treatments and 6 replications, with one eucalyptus plant per experimental unit (18L pot), totaling 36 experimental units. The treatments consisted of biostimulant concentrations: T0 (0 mL/L), T1 (5 mL/L), T2 (10 mL/L), T3 (100 mL/L), T4 (500 mL/L) and T5 (1000 mL/L). During the experiment, the variables aerial part height and stem diameter were measured weekly. At the end, at 99 days, data on aerial part height (HT), stem diameter (DC), aerial part dry mass (MSPA), root dry mass (MSR), total dry mass (MST), Dickson quality index (IQD), shoot height/shoot dry mass ratio (RAMPA), shoot/root ratio (RPAR), shoot/diameter ratio (RAD) and leaf water potential (Ψw,), for physiological analysis. The application of Stimulate® provided significant results in all variables measured, highlighting treatment T2, in most of the variables evaluated. Treatment T1 was less sensitive to water stress on the second, third and fourth day. It is concluded that the use of Stimulate® can be a viable option to increase the survival of seedlings in the field, in critical stages of establishment, presented greater gains in photosynthetic tissue, productivity, good quality standard of seedlings, more lignified and lesser seedlings. sensitive to water stress.